Chijabyukpi-Tang Inhibits Pro-Inflammatory Cytokines and Chemokines via the Nrf2/HO-1 Signaling Pathway in TNF-α/IFN-γ-Stimulated HaCaT Cells and Ameliorates 2,4-Dinitrochlorobenzene-Induced Atopic Dermatitis-Like Skin Lesions in Mice - Lee, Ji-Hyun (Front Pharmacol, 2020)
Chijabyukpi-tang (CBT) is an oriental herbal formula consisting of three herbs (Gardeniae Fructus (Gardenia jasminoides J.Ellis.), Phellodendri Cortex (Phellodendron amurense Rupr.), Glycyrrhizae Radix (Glycyrrhiza uralensis Fisch. ex DC.) at the ratio of 2: 2: 1. CBT has traditionally been used to treat eczema with inflammation in Northeast Asia. The components of CBT have been shown to have anti-inflammatory and anti-oxidant properties, but the exact role and mechanism of CBT on atopic dermatitis (AD) remain unclear. In this study, we investigated the anti-inflammatory effect and mechanism of CBT in the HaCaT human keratinocyte cell line and investigated the anti-atopic effect in mice models of atopic dermatitis-like skin lesions. In the tumor necrosis factor alpha (TNF)-α/interferon (IFN)-γ-stimulated HaCaT cells, CBT inhibited the production of pro-inflammatory cytokines and chemokines and elevated the nuclear translocation of NF-E2 p45 related factors 2 (Nrf2) and subsequent production of heme oxygenase-1 (HO-1). CBT improved the symptoms of atopic dermatitis-like lesions in 2,4-dinitrochlorobenzene (DNCB)-treated mice by suppressing the levels of serum immunoglobulin E (IgE), and various pro-inflammatory cytokines and chemokines. The improvement effect of CBT on atopic dermatitis-like lesions can be predicted to be due to increased Nrf2 and HO-1 gene expression. These results suggest that CBT is an herbal medicine with the potential for use as a therapeutic agent for inflammatory skin diseases such as atopic dermatitis.